Distributions and Abundances of Sublineages of the N2-Fixing Cyanobacterium Candidatus Atelocyanobacterium thalassa (UCYN-A) in the New Caledonian Coral Lagoon - Henke, Britt A.; Turk-Kubo, Kendra A.; Bonnet, Sophie; Zehr, Jonathan P. (Frontiers in Microbiology, 2018)
Nitrogen (N2) fixation is a major source of nitrogen that supports primary production in the vast oligotrophic areas of the world’s oceans. The Western Tropical South Pacific has recently been identified as a hotspot for N2 fixation. In the Noumea lagoon (coastal New Caledonia), high abundances of the unicellular N2-fixing cyanobacteria group A (UCYN-A), coupled with daytime N2 fixation rates associated with the < 10 µm size fraction, suggest UCYN-A may be an important diazotroph (N2-fixer) in this region. However, little is known about the seasonal variability and diversity of UCYN-A there. To assess this, surface waters from a 12 km transect from the mouth of the Dumbea River to the Dumbea Pass were sampled monthly between July, 2012 and March, 2014. UCYN-A abundances for two of the defined sublineages, UCYN-A1 and UCYN-A2, were quantified using qPCR targeting the nifH gene, and the nifH-based diversity of UCYN-A was characterized by identifying oligotypes, alternative taxonomic units defined by nucleotide positons with high variability. UCYN-A abundances were dominated by the UCYN-A1 sublineage, peaked in September and October and could be predicted by a suite of nine environmental parameters. At the sublineage level, UCYN-A1 abundances could be predicted based on lower temperatures (<23C), nitrate concentrations, precipitation, and wind speed, while UCYN-A2 abundances could be predicted based on silica, and chlorophyll a concentrations, wind direction, precipitation, and wind speed. Using UCYN-A nifH oligotyping, similar environmental variables explained the relative abundances of sublineages and their associated oligotypes, with the notable exception of the UCYN-A2 oligotype (oligo43) which had relative abundance patterns distinct from the dominant UCYN-A2 oligotype (oligo3). The results support an emerging pattern that UCYN-A is comprised of a diverse group of strains, with sublineages that may have different ecological niches. By identifying environmental factors that influence the composition and abundance of UCYN-A sublineages, this study helps to explain global UCYN-A abundance patterns, and is important for understanding the significance of N2 fixation at local and global scales.